(untitled) (Actualizaciones en Sida e Infectología, 2022)
We are in times of accelerated events. News, novel infections, as well as the identification of solutions, occur at unprecedented speeds. As a result of the COVID-19 pandemics, it has become apparent that health care systems can rapidly change and adjust to new challenges, and some of these changes can be leveraged to end AIDS as a public health issue by 2030. There are plenty of tools available, but a sense of urgency is needed to seek their implementation. Pre-exposure prophylaxis (PrEP), a biomedical intervention that is part of the combination prevention package, is 99% effective when taken correctly, safe, easy to administrate, and available at very low cost if unified purchases are made (1). Its use showed a consistent long-term reduction of the incidence of AIDS cases in Australia (2), which findings were later repeated in London and San Francisco. However, throughout the world, and particularly in the Latin American region, the number of persons who initiate PrEP each year is well below the number of persons who are at significant risk of getting HIV, and extending these programs to meet the proposed target of 10,000,000 people receiving PrEP by 2025 is urgent (3). In Brazil, prescription by nurse staff and follow-up through telemedicine facilitated the follow-up during the COVID-19 pandemics. PrEP programs not only reduce the risk of getting HIV, but are also essential to provide sexual health information, afford an opportunity to get vaccinated against the human papillomavirus and viral hepatitis, and allow for the identification and treatment of sexually transmitted infections (STIs) among PrEP users and their contacts. In fact, mathematic models and certain local experiences show that, through systematic screening and treatment of STIs, it is possible to reduce the prevalence of infections, especially by Neisseria gonorrhoeae (4, 5). Post-exposure prophylaxis (PEP) with doxycycline can reduce the incidence of syphilis, although the potential impact on resistance is still unknown (6). But the greatest benefit of the PrEP programs has been proving the importance of working with Non-Governmental Organizations (NGOs) and Civil Society Organizations (CSOs) which provide services to better serve the most affected populations. As a result of such interaction, it has been possible to draw attention to and raise awareness of the individual work of each one of us, forcing conversation about sexuality in order to assess the risks, leaving prejudice and discrimination aside, embracing diversity. The World Health Organization Guideline on prevention for key populations proposes new recommendations and guidelines for HIV, STI, and viral hepatitis prevention among men who have sex with men, trans and gender diverse people, sex workers, injecting drug users, and imprisoned or confined persons (7). Adding long-acting injectables to PrEP can facilitate the use of this tool in the future. Strategic use of resources to diagnose cases is a key factor. A small group of recently infected people contribute to a third of the new infections due to extremely high viral load during acute infection (8), and half occur in people who are unaware of their status. Therefore, any efforts to raise awareness among key populations of the symptoms of acute infection and the need to submit to and periodically repeat tests will have a significant impact if access to tests is provided. Finally, prompt treatment of all positive persons under an integrase-inhibitor based schedule leads to rapid reduction of community viral load (9, 10). Additionally, due to the availability of fixed-dose combinations of generic dolutegravir, this intervention is highly cost-effective. The expansion of diagnosis and the rapid initiation of treatment can potentially reduce the impact of late diagnosis on HIV mortality. It is estimated that 86% of deaths occurred within the first year from diagnosis are due to late diagnosis (11). There are rapid tests for the detection of histoplasmosis, tuberculosis and cryptococcosis antigens. Use of such tests, together with tuberculosis molecular tests for sputum-producing patients, can reduce mortality by up to 10% (12). A recent review collected 27 digital interventions which can improve results in the HIV care continuum (13). Then, if we are determined to end HIV as a public health issue by 2030, it is important to focus our work on making certain major changes and to leverage on certain available innovations: • Significantly increasing the number of HIV tests performed, especially to key population youth and to people having any signs of infection, including detection by emergency services, among hospitalized patients, and in tuberculosis and STI programs, until a significant reduction of late diagnosis and the number of people unaware of their diagnosis is achieved. • Training NGOs, CSOs, communities, and primary and emergency care services on the detection of acute infection symptoms regarding criteria to suspect HIV chronic infection and on diagnostic tools. • Ensuring the availability and expansion of the HIV autotest, promoting PEP as a point of entry to PrEP programs, and expanding PrEP programs based on updated population estimates, reducing obstacles to their implementation. • Improving the availability of fixed-dose dolutegravir-based treatment across all health subsystems, and promoting same-day initiation of treatment under this schedule. • Involving NGOs and CSOs which work with key populations in dissemination campaigns, testing, providing PrEP, and immediate connection with antiretroviral treatment (ART). Exploring ART decentralization or initiation processes at least during the first month of treatment until connection with the follow-up service is achieved. • Promoting the transition from complex (protease inhibitors) or higher toxicity (efavirenz) schedules to dolutegravir, even in children older than four weeks or people with tuberculosis. • Establishing social and clinical research platforms for the assessment of new interventions to reduce incidence, accelerate treatment, or improve viral suppression. • Periodically reviewing targets, establishing continuous improvement mechanisms, prioritizing the HIV elimination agenda, and proposing collective construction spaces to get to those who are still out of reach. Rapid and effective implementation of these activities through an integrated package may reposition Latin America as a global leader in HIV response and makes it possible to dream of putting an end to HIV as a public health issue until a vaccine becomes available.